Peningkatan praktek gizi seimbang dan PHBS Pada murid sekolah dasar - Saifuddin Sirajuddin; Masni Masni; Ulfa Najamuddin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Short and thin nutritional problems faced by students in Cambaya Elementary School in Makassar City are still high at 39.4% and 23.1% respectively. Breakfast habits that are very low at only 22.1% have the potential to cause stunted growth and development of the child's brain, which has implications for the decrease in intelligence of the child. This research aims to improve the knowledge, motivation, and skills of parents and teachers about balanced nutrition of school children and improving students' practice and motivation in a clean and healthy environment. The research uses quasi-experimental methods with pre and post test designs. The population in this study were 50th grade students of the Makassar Cambayya state primary school. Implementation of activities in the form of lectures, discussions, balanced nutrition practices and PHBS. Knowledge, motivation, skills about balanced nutrition and PHBS were measured using a questionnaire. Assessment is carried out before and shortly after giving counseling and a week after giving counseling. The results of this service are based on the Wilcoxon test. It is known that there is a significant increase in knowledge before and shortly after giving counseling p = 0.039 (p <0.05) and a decrease in knowledge a week after counseling p = 0.011 (p <0.05). Suggestions that can be given to the school should be active in conveying information about PHBS to school children.